Rancang Bangun Perangkap Tikus Jenis Falling Floor Trap Menggunakan Dengan Notifikasi Android Berbasis Mikrokontroler - Abdul Hamid; Budi Rahmadya; Arrya Anandika (Universitas Andalas, 2023)
This Study aims to create a Falling Floor type of Rats Trap that can automatically catches and kills rats that enter the trap and then, it will send a notification to the user’s phone via telegram chat app also automatically set it back to steady state again once the times given to kill the rat is over by using a sensor while system is controlled by a microcontroller. The system consists several main components that construct the system, first Wemos D1 “a wifi connections ready microcontroller” that controls whole system, an ultrasonic sensor as the main input, it detects the range of the sensor from the rat that enter the trap, the exact range will be determined as the the right condition so that system says a rat is detected, servo motors that used as rat traps mechanic that move each exact part of rat traps, like moves the rat enter‘s door, moves the trap floor, and moves the fences insde the rat cage, and especially systems should be connected to an internet connection by the wemos D1, so that system can sends a notification to user’s phone if a rat caught by the system with overall success rate is 67%.